Construction Industry: Green Building - Yeh, Lu-Tsou (Recent Research Reviews Journal, 2023)
As a result of the advantages for the environment, economy, and society, recent developments in green building technologies (GBTs) have increased significantly. For projects to develop green buildings, technology is vital. A number of green building technologies, such as those that reduce temperature, have wastewater systems, are energy-efficient, and have cooling systems powered by solar energy, GBT has the ability to advance in the direction of sustainable development, with a focus on climate change. The basic goal of the GBT is to make use of water, electricity, and other resources efficiently and in an appropriate way. The environment will be improved as a result, such as by reducing pollution and the use of energy, improving productivity and wellness, and reducing maintenance and operating costs. There is a lack of critical analysis of either previous or current studies performed in the green building technology (GBT) industry to determine the future pathway for sustainable green building technologies. With the use of the appropriate research methods, a critical review was found. A building information model (BIM) and ontology are used in green buildings to handle multidisciplinary operations. The combination of SWRL and OWL models built on the Jess rule engine increases the building efficiency. Sustainable materials made from industrial scrap help to mitigate the environmental impact of carbon emissions. The use of various activators increases the flexibility, strength, and volume of these materials. Sensors, the environment, and other external forces all play a role in how smart materials function. This study summarizes the green building and their assessment tools, aspects, how much the green buildings are benefits to the environment, humans, and economy, the technologies used in green buildings in construction industries, and the factors that affect the green building technology.